Novel Service Delivery Approach to Address Reproductive Health Disparities within Immigrant Latino Communities in Geographic Hot Spots: An Implementation Study. Issue 3 (6th July 2020) - Parker, Amittia; Johnson-Motoyama, Michelle; Mariscal, E Susana; Guilamo-Ramos, Vincent; Reynoso, Elizabeth; Fernandez, Cielo
Abstract: Latinx youths continue to have the highest rates of teenage births in the United States and are at increased risk of acquiring sexually transmitted infections, including HIV/AIDS. A community-based research partnership piloted Families Talking Together, a brief, parent-based sexual risk reduction program using a novel and culturally relevant approach. This mixed-methods study examined the feasibility and acceptability of Spanish-speaking promotoras de salud (that is, community health workers) as implementers of an evidence-based intervention (EBI) to reach underserved immigrant communities. Findings suggest that promotoras are capable of implementing the EBI with positive organizational, client, and implementation outcomes. Furthermore, promotoras hold particular promise for addressing reproductive health disparities as they are indigenous and trusted members of the community who can reach members of marginalized Latino populations.